suppose f: R-->R is invertible and C Є R is a constant
find an expression for the inverse of g(x) = f(x+c) in terms of f^-1
and if c is not equal to 0 than find an expression for the inverse of h(x) =f(cx) in terms of f^-1
suppose f: R-->R is invertible and C Є R is a constant
find an expression for the inverse of g(x) = f(x+c) in terms of f^-1
and if c is not equal to 0 than find an expression for the inverse of h(x) =f(cx) in terms of f^-1
thanks
Suppose that . Then
Do the second part in a similar way, starting with , and so